Radiochemical analysis of bottled drinking waters consumed in Turkey and a risk assessment study - Turhan, Ş.; Zriba, N.A.E.M.; Taşkın, H.; Yılmaz, Z.; Bayülken, S.; Hançerlioğulları, A.; Kurnaz, A. (Elsevier BV, 2019)
Abstract Water is of vital importance for human life and health. Therefore, drinking water must be safe and quality enough to be consumed by humans. In this study, 19 commercially available Turkish brands of bottled drinking water (BDW) were analyzed to assess the radiological and chemical quality of these waters. The radioactivity concentrations of gross alpha and beta in BDW samples were determined by using a gas proportional α/β counter. The average gross alpha and beta radioactivity concentrations were 21 ± 5 mBq/L and 59 ± 12 mBq/L, respectively. The average annual effective radiation doses due to consumption of BDW samples were estimated as 8, 12 and 24 μSv/y for infant, children and adult, respectively. The concentrations of anions (fluoride, chloride, bromide, nitrate, nitrite, sulfate and phosphate) and cations (Mg, Sr, Fe, Pb, Hg, Zn, Cr, Co, Ni, Cd and Mn) in BDW samples were determined using an ion chromatography system and inductively coupled plasma- optical emission spectrometry, respectively. The average concentrations of fluoride, chloride, nitrate and sulfate were determined as 32.1, 1882.5, 2050.7 and 4776.9 μg/L, respectively. The average concentrations of Mg, Sr, Fe, Pb, Hg, Zn, Cr, Co, Ni, Cd and Mn were found as 2899.0, 62.9, 3.45, 3.18, 2.0, 2.0, 1.9, 1.7, 1.7, 1.2 and 1.0 μg/L, respectively. The results reveal that all radiological and chemical values measured in BDW samples, except for Hg, are lower than the limit values set by national regulations and World Health Organization. The average Hg concentration is higher than the limit values set by national regulations.
Keywords: 13. Climate action; 6. Clean water; 3. Good health